Penyegaran Keterampilan Dasar Bekerja di Laboratorium Mikrobiologi untuk Persiapan Tugas Akhir dan Menghadapi Dunia Kerja - Wira Eka Putra; Mardiana Lelitawati; Intan Chairun Nisa; Evi Susanti; Salsabila Kasta Hygiea Iswara; Syafira Maharani (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
Basic laboratory skills are essential for supporting the quality of learning outcomes and processes, and they are also very beneficial as preparation for the workplace. The goal of this activity is for students and graduates of the Faculty of Mathematics and Natural Sciences (FMIPA) to refresh and develop their basic abilities in working in a microbiological laboratory in preparation for their final assignment and the workplace. During COVID-19 pandemic, the agenda is carried out in two methods, namely online and offline systems. The training was conducted online using a video conferencing platform and an online academic information system, as well as offline at the microbiology laboratory, Department of Biology, FMIPA, Universitas Negeri Malang. The participants' comprehension of basic microbiology concepts and basic abilities for working in a microbiology laboratory improved as a result of this exercise according to the pretest and posttest result.